Effect of bypass protein supplement on milk production in Jersey cow: Bypass protein supplementation in dairy cow - Tiwari, MR; Jha, PK; Pant, SR; Acharya, MP; Thapa, P; Shrestha, BK (Bangladesh Journal of Animal Science, 2018)
Bypass protein is known to stimulate the voluntary feed intake, increase quality milk production and thereby improve economic status from dairy cows farming. This study was conducted to compare the responses of additional bypass protein as feed supplement on milk production performance in Jersey dairy cows, and its cost benefits per L of milk production. A total of 12 lactating Jersey dairy cows, apparently having similar reproductive and productive performances were selected. The cows were randomly grouped into 3 treatments groups; T1 (Control): 6 kg concentrate mixture, T2: 6 kg concentrate mixture plus 1.5 kg heat-treated soybean cake, and T3: 6 kg concentrate mixture plus 1.5 kg formalin treated soybean cake. An acclimatization period of 7 days, the experimental procedure was carried for the period of 62 days. Other management; feeding - adlib amount of straw and green grass such as oat, signal and local grass once a day, natural grazing average 3 hrs/ day), watering and housing remained as routinely done by the farm. The compound feed was procured from Fine Feeds Industries Pvt. Ltd., Chitwan, Nepal. Feed intake and milk production of individual animal was recorded daily. The straw and concentrate intake of experimental cows among the treatment groups differed significantly (P<0.001), whereas green grass intake among the diet groups differed insignificantly. The initial recorded milk production 5.4 L, 5.45 L and 5.62 L among the treatment groups found insignificant, whereas the final milk production 7.85 L, 6.12 L and 5.82 L among the treatment groups found highly significant (P<0.001). The economic analysis (its cost benefits per L of milk production) during the period of 62 days of experimentation, it was revealed that feeding package T2 is more beneficial than T3. The net income accounted for NRs 12152.11 and NRs 7457. 55 using T2 and T3 feeding package, respectively. Therefore, it is suggested that heat-treated soybean cake supplementation to early lactating (up to 3 months) dairy cows is one of the option to increase milk production and income of farmers. Further study needed to be carried out to ascertain the optimum level and duration of additional protein supplementation to dairy cows. Bang. J. Anim. Sci. 2018. 47 (2): 98-104